2003
DOI: 10.1002/art.11337
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for radiographic progression, radiographic damage, and disability in juvenile idiopathic arthritis

Abstract: Objective. To investigate the rate of radiographic progression and identify prognostic factors of radiographic progression, radiographic damage, and physical disability in juvenile idiopathic arthritis (JIA).Methods. Ninety-four JIA patients with a median disease duration of 1.1 years were followed up prospectively for a median of 4.5 years. Bilateral wrist radiographs were obtained at baseline, at 1 year, and at the last followup visit. Radiographic damage was assessed by the carpal length (Poznanski score), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 28 publications
2
77
0
12
Order By: Relevance
“…This sign is considered a key manifestation of JIA (8,11,12), but in our investigations, its reproducibility was moderate (9). Definitions of growth disturbance therefore need further refinement (e.g., an atlas of reference films) to improve the value in a scoring system.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This sign is considered a key manifestation of JIA (8,11,12), but in our investigations, its reproducibility was moderate (9). Definitions of growth disturbance therefore need further refinement (e.g., an atlas of reference films) to improve the value in a scoring system.…”
Section: Discussionmentioning
confidence: 66%
“…Because one of the aims of JIA treatment is to prevent or retard joint damage, and radiographs are able to document this damage, a standardized tool for the radiologic evaluation of the lesions of the joints over time is needed. Several methods have been proposed to assess radiographs in JIA (5)(6)(7)(8), but none have been tested for sensitivity to change or discrimination between treatment groups in a trial. Recently, we introduced the Dijkstra score as a standardized method to evaluate the radiographs of patients with oligoarticular-and polyarticular-onset JIA.…”
mentioning
confidence: 99%
“…In patients with wrist involvement, standard radiographs of both wrists in the posteroanterior view were obtained. Radiographic damage was scored according to the method described by Poznanski et al (12), as previously reported (13). Briefly, this method is based on the measurement of the radiometacarpal (RM) length, which is the distance from the base of the third metacarpal bone to the midpoint of the distal growth plate of the radius, and of the maximal length of the second metacarpal bone (M2).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, radiographs do not measure damage in extraarticular systems or visceral organs. Second, the few available methods for scoring radiographic damage in JIA patients concentrate on the wrists or knees (12)(13)(14), whereas damage in other joints may be of equal importance for a patient's functional ability. Third, the cost of measuring radiographic damage and the related radiation exposure make these methods less suitable for studying large numbers of patients or for use in developing countries.…”
mentioning
confidence: 99%
“…Juvenile idiopathic arthritis US is an accurate test for intraarticular signs of disease, such as joint effusion, synovial hypertrophy and hyperaemia, and is able to detect subclinical synovitis in children with juvenile idiopathic arthritis [26,27]. The ability of US to assess multiple joints in one sitting, and to detect subclinical synovitis, seems to be particularly useful in juvenile idiopathic arthritis, since the differentiation of oligoarthritis and polyarthritis is based on the number of inflamed joints.…”
Section: Inflammatory and Degenerative Arthropathiesmentioning
confidence: 99%